The Students’ Perceptions of Moodle-based LMS in English Learning - Tri Wintolo Apoko (Edumaspul: Jurnal Pendidikan, 2022)
This research aimed at investigating the students’ perceptions of Moodle-based LMS in English learning and the benefits of using Moodle for the students. There were 94 students or respondents from one of the private universities in Jakarta used to describe the data as well as to analyze it. The method used in this research was a survey with qualitative description. A questionnaire was used to collect the data. The result showed that there were positive responses of the students dealing with Moodle-based LMS in online learning asynchronously. It was therefore expected that lecturers should have been able to develop and design more learning contents or materials and the activities to upload as online learning better in the future.